The news construction of indigenous peoples in the main online newspapers of Argentina - Pereyra, Rocío (2021)
This article arises from the interrelation of different theoretical and methodological perspectives in the areas of Communication and Anthropology in order to analyze the media treatment of the situation of indigenous peoples in Argentine territory. To do this, theoretical concepts of the Agenda Setting theory were operationalized and a content analysis was developed from the collection of journalistic articles from the most far-reaching online information portals in Argentina, in the period from August 2018 to June, 2019. The conclusions show: a low information coverage on the subject; the construction and reproduction of meanings and representations around native peoples linked to the reinforcement of stereotypes and prejudices; and little opportunity for them to be actors and sources of information.